2005
DOI: 10.3390/i6120303
|View full text |Cite
|
Sign up to set email alerts
|

Facile Interfacial Electron Transfer of Hemoglobin

Abstract: Abstract:We herein describe a method of depositing hemoglobin (Hb) and sulfonated polyaniline (SPAN) on GC electrodes that facilitate interfacial protein electron transfer. Well-defined, reproducible, chemically reversible peaks of Hb and SPAN can be obtained in our experiments. We also observed enhanced peroxidase activity of Hb in SPAN films. These results clearly showed that SPAN worked as molecular wires and effectively exchanged electrons between Hb and electrodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…Over recent years, carbon nanomaterials [11][12][13], metal oxides [14], metal nanoparticles [15], ionic liquids [16] and conducting polymers [17] have been utilized as immobilization matrices for Hb. In particular, the 2D carbon nanomaterial graphene (GR) exhibits electronic conductivity and thermal stability superior to other carbon nanoforms [18,19], and make it an ideal support material in the fabrication of biosensors [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Over recent years, carbon nanomaterials [11][12][13], metal oxides [14], metal nanoparticles [15], ionic liquids [16] and conducting polymers [17] have been utilized as immobilization matrices for Hb. In particular, the 2D carbon nanomaterial graphene (GR) exhibits electronic conductivity and thermal stability superior to other carbon nanoforms [18,19], and make it an ideal support material in the fabrication of biosensors [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…An apparent activation energy Ea was calculated from the slope of the line to be 22.8 kJ·mol −1 , which is smaller compared with the activation energy for enzyme-catalyzed reactions (20-85 kJ·mol −1 ). One of the reasons for the small apparent activation energy is probably the catalytic effect of polyaniline on the oxidation of H 2 O 2 [12] . Also, this is why the operational potential of the biosensor can be controlled lower than that of other choline biosensors [1] .…”
Section: Effect Of Temperature On the Response Current Of The Biosensormentioning
confidence: 99%
“…Therefore, polyaniline could function as "moleculewires" to relay electron transfer [12] , which is in favor of the electron transfer in the enzyme-catalyzed reactions. Such properties of polyaniline offer a possibility for the oxidation of H 2 O 2 at lower potentials.…”
Section: Introductionmentioning
confidence: 99%
“…Ngamna et al have immobilized horseradish peroxidase poly(2methsulphonated polyaniline-5-sulphonic acid)/l-lysine composite [127]. Zhou et al have observed enhanced peroxidase activity in hemoglobin in sulfonated polyaniline on glassy carbon electrodes [128]. This result has been attributed to the facile interfacial transfer of hemoglobin mediated by sulphonated polyaniline.…”
Section: Enzymosensorsmentioning
confidence: 99%